Analysis of The Influence of Digital Marketing Capability And Product Innovation on The Marketing Performance of Msmes In The Culinary Sector : Penelitian - Marcelitha Tabita Montolalu; Muhammad Fikri Maulana; Marjuki; Hamdiah; Donald Michi Kasetty (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector operate in a hyper-competitive market characterized by low entry barriers and rapidly changing consumer preferences. This study analyzes the critical impact of digital marketing capability and product innovation on the marketing performance of culinary MSMEs. Drawing on the Resource-Based View (RBV) and Dynamic Capabilities theory, this research investigates how local food entrepreneurs leverage digital technologies and unique product developments to achieve a sustainable competitive advantage. Utilizing a quantitative survey methodology with data collected from culinary MSMEs, the research framework is examined using Structural Equation Modeling (SEM). The empirical findings demonstrate that both digital marketing capability and continuous product innovation exert a positive and highly significant influence on marketing performance, measured through sales growth, customer retention, and market share expansion. Furthermore, the integration of digital agility accelerates market responsiveness, allowing innovations to be commercialized more effectively. The study concludes with tactical frameworks for MSME owners and regional policymakers to optimize digital literacy and foster collaborative innovation ecosystems to sustain rural and urban economic resilience.